Pengaruh Parabahasa Aceh Besar terhadap Penafsiran Pesan - Cut Lusi Chairun Nisak (Program Studi Ilmu Komunikasi FISIP Universitas Syiah Kuala, 2017)
This research aims to learn the extent to which the Aceh Besar's paralinguistic features affect the interpretation of the message by the students at Syiah Kuala University. The study employed the quantitative method by distributing questionnaires to 100 respondents in 10 faculties of Unsyiah selected using the stratified random sampling technique. The results show that the t value of the paralinguistic variable was 3,820 while t table was 1.984 at α = 5%. The result indicates that t value (3,820) is greater than t table (1,984), thus Ha is accepted and Ho is rejected. It means that the Aceh Besar’s paralinguistic features positively and significantly affect the interpretation of spoken messages.